Loshadi i poni - Travina, I. V. (Irina Vladimirovna) (Wonders of learning., 2016)
Have you ever thought about the effort it takes to care for a pony or a horse? Well, here is your very own personal guide to taking care of a horse or a pony. It is interesting, factual and is complemented with an array of brilliant photography.